2018
DOI: 10.1017/s1355617718000176
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and Recovery of Different Neglect-Related Symptoms in Right Hemisphere Infarct Patients during a 1-Year Follow-Up

Abstract: During the first year after RH infarct, originally left-sided manifestation of neglect shifted toward milder non-lateralized attentional deficit. Ipsilateral orienting bias and slowed processing speed appeared to be rather persistent neglect-related symptoms both in neglect patients and patients with initially milder inattention. We propose some effortless, tentative ways of examining processing speed and ipsilateral orienting bias alongside the BIT to better recognize these neglect-related symptoms, and highl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 54 publications
(156 reference statements)
2
7
1
Order By: Relevance
“…RH patients did not show spatial bias in either version of the Twinkle Task, even though the increase in the visual angle was massive and performance was analyzed with multiple parameters in addition to omissions. Unlike in previous studies (Azouvi et al, 2002;Nurmi et al, 2010Nurmi et al, , 2018Basagni et al, 2017;Priftis et al, 2019), analyzing starting points, increasing perceptual demands, or limiting performance time had no sensitivity increment effect in detecting spatial bias in the group of RH patients. Standard, paper-and-pencil approaches are maximally informative in acute stroke, and with rather severe cases.…”
Section: Discussioncontrasting
confidence: 85%
See 1 more Smart Citation
“…RH patients did not show spatial bias in either version of the Twinkle Task, even though the increase in the visual angle was massive and performance was analyzed with multiple parameters in addition to omissions. Unlike in previous studies (Azouvi et al, 2002;Nurmi et al, 2010Nurmi et al, , 2018Basagni et al, 2017;Priftis et al, 2019), analyzing starting points, increasing perceptual demands, or limiting performance time had no sensitivity increment effect in detecting spatial bias in the group of RH patients. Standard, paper-and-pencil approaches are maximally informative in acute stroke, and with rather severe cases.…”
Section: Discussioncontrasting
confidence: 85%
“…To prevent compensation and to identify milder deficits, time limits are sometimes introduced (Priftis et al, 2019). Another possibility is to calculate indices that are more sophisticated than the simple number of omissions, such as the starting point analysis (Azouvi et al, 2002;Nurmi et al, 2010Nurmi et al, , 2018, which allows quantifying neglect patients' tendency to start visual searching from the ipsilesional hemispace (Kinsbourne, 1987;Karnath, 1988;Olk et al, 2002). Despite these efforts, several studies have demonstrated that computer tasks, which are complex, and require high attentional demands, are more sensitive than paper-and-pencil cancellation tasks (Deouell et al, 2005;List et al, 2008;Rengachary et al, 2009;Bonato et al, 2010Bonato et al, , 2012Blini et al, 2016;Andres et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Chronic patients often manifest such persisting attention deficits that affect both sides of space (Corbetta & Shulman, 2011;Husain & Rorden, 2003;Manly, 2002;Robertson, 1993; van Kessel, van Nes, Brouwer, Geurts, & Fasotti, 2010), and complain about severe and long-lasting impairment in the ability to maintain concentration when reading, following TV programmes, or engaging in other prolonged activities such as therapy sessions. In a recent study by Nurmi and colleagues (Nurmi et al, 2018), the researchers followed patients with mild neglect in their first year after stroke and observed a longitudinal reduction in spatial bias as measured on cancellation tasks, with omissions becoming evenly distributed in space -a pattern which indicates persisting non-lateralised deficits, rather than ongoing pathological lateralised bias. This is also reflected in our clinical experience working with patients affected by severe neglect at presentation, who often demonstrate a non-lateralised pattern of omissions when re-tested in later stages post-stroke (Figure 2).…”
Section: Non-lateralised Deficits In Neglectmentioning
confidence: 99%
“…However, an association between slowed processing speed and neglect was reported in a longitudinal study up to one year after stroke. 28 In that study, right hemispheric stroke patients with acute neglect or milder forms of left-sided inattention showed a significantly slower processing speed in the acute phase, at 6 months, and at 12 months after stroke compared to healthy controls. The association between long-term lateralized inattention and early processing speed is interesting since previous stroke studies have suggested that decreased speed appears to underlie cognitive dysfunction in different domains such as visuoperceptual function and executive function.…”
Section: Discussionmentioning
confidence: 79%
“…To our knowledge, an association between processing speed at the early phase after stroke and occurrence of long‐term neglect or lateralized inattention has not been previously investigated. However, an association between slowed processing speed and neglect was reported in a longitudinal study up to one year after stroke . In that study, right hemispheric stroke patients with acute neglect or milder forms of left‐sided inattention showed a significantly slower processing speed in the acute phase, at 6 months, and at 12 months after stroke compared to healthy controls.…”
Section: Discussionmentioning
confidence: 89%